2009
DOI: 10.1002/gps.2297
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Lewy body disease in patients with late‐onset depression, anxiety and psychotic disorder with myocardial meta‐iodobenzylguanidine scintigraphy

Abstract: Group VH was considered to DLBD, and Group PCD was regarded as PDD or DLBD with early psychotic presentation. Group DA has a possibility of early depression or anxiety disorder of LBD although it lacked DLBD criteria. Atypical Parkinsonian syndromes are associated with cognitive disturbance irrespective of psychiatric profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…The comprehensive computer literature search from the PubMed/MEDLINE and Embase databases revealed 71 articles (Fig 1). Reviewing titles and abstracts, 41 articles were excluded because they did not present any diagnostic information; 30 articles were selected 12–41 . These 30 studies were retrieved in full‐text version; an additional study was found screening the references of these articles 42 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comprehensive computer literature search from the PubMed/MEDLINE and Embase databases revealed 71 articles (Fig 1). Reviewing titles and abstracts, 41 articles were excluded because they did not present any diagnostic information; 30 articles were selected 12–41 . These 30 studies were retrieved in full‐text version; an additional study was found screening the references of these articles 42 .…”
Section: Resultsmentioning
confidence: 99%
“…These 30 studies were retrieved in full‐text version; an additional study was found screening the references of these articles 42 . From these 31 articles potentially eligible for inclusion, after reviewing the full‐text article, one study was excluded as case report; 23 one article was excluded because sensitivity and specificity of MIBG scintigraphy in the subset of DLB population could not be calculated for insufficient data; 12 seven articles were excluded because there was an overlap of patient data in other studies; 20,24,26,29,31,34,40 12 articles were excluded because MIBG scintigraphy was not performed in patients with other dementia than LBD; 13–16,19,21,25,28,32,35,36,38 two articles were excluded because less than 6 patients with DLB were included 37,42 …”
Section: Resultsmentioning
confidence: 99%
“…Psychiatric condition is still unclear in individuals with incidental LBD and PPP. In our previous study psychiatric features could be classified into three groups, and each of them had clinical distinctive characteristics in MIBG‐verified patients (Kobayashi et al ., ). The purpose of the present study is to examine whether PPP can be identified or not in setting of psychiatric clinic with more numbers of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety is also increasingly recognized (independently from depression) as a common symptom in older adults individuals living with various aetiologies of dementia, including Alzheimer's disease, vascular dementia, frontotemporal dementia, Lewy body disease, posterior cortical atrophy, dementia associated with Parkinson's disease, and in subjective and mild cognitive impairment, tending to result in poorer quality of life, problematic behaviours, limitations in activities of daily living, nighttime awakening and poorer neuropsychological performance [43,65,69,[77][78][79][80][81][82][83][84][85]. The relationship between anxiety and dementia is however both complex and controversial with overlap between the symptoms of anxiety and dementia and other behavioral and psychological problems such as agitation and depression [10,12,43,62,65,71,73,77,82,[86][87][88].…”
Section: The Potential Impact Of Anxietymentioning
confidence: 99%